Engineering the Thermal Conductivity of Doped SiGe by Mass Variance: A First-Principles Proof of Concept - Hahn, Konstanze R.; Melis, Claudio; Bernardini, Fabio; Colombo, Luciano (Frontiers in Mechanical Engineering, 2021)
Thermal conductivity of bulk Si0.5Ge0.5 at room temperature has been calculated using density functional perturbation theory and the phonon Boltzmann transport equation. Within the virtual crystal approximation, second and third order interatomic force constants have been calculated to obtain anharmonic phonon scattering terms. An additional scattering term is introduced to account for mass disorder in the alloy. In the same way, mass disorder resulting from n- and p-type dopants with different concentrations has been included, considering doping with III-group elements (p-type) B, Al and Ga and with V-group elements (n-type) N, P and As. Little effect on the thermal conductivity is observed for all dopants with a concentration below 10^21 1/cm^3. At higher concentration, reduction by up to 50% is instead observed with B-doping in agreement with the highest mass variance. Interestingly, the thermal conductivity even increases with respect to the pristine value for dopants Ga and As. This results from a decrease in the mass variance in the doped alloy, which can be considered a ternary system. Results are compared to the analogous effect on the thermal conductivity in doped Si.